Analysis of the Factors Influencing Shopping Decisions inOnline Shop Students in the Management Economics Study Program at Graha Nusantara University Padamgsidimpuan - Nirmala Hati Harahap; Nurdelila Nurdelila; Ade Maya Mei Shanty (Al-Kharaj: Journal of Islamic Economic and Business, 2022)
The purpose of this study was to find out (1) what factors influenced students in buying at online stores and (2) what factors most dominantly influenced purchasing decisions at online stores by students of the Management Economics Study Program at Graha Nusantara University. This research is a factorial research. The population in this study were all 68 students of the Management Economics Study Program class of 2020 and were analyzed using factor analysis. The results of the study show, (1) there are four factors that influence purchasing decisions at student online shops, namely (1) product quality; (2) convenience; (3) information quality; and (4) consumer trust. The magnitude of the variance explains the successive factors, namely product quality 68.934%, convenience 28.744%, information quality 1.470%, and consumer trust 0.853%. (2) the most dominant factor influencing purchasing decisions at the online shop of 2020 Management Economics Study Program students is product quality with an Explain variance of 68.934%, meaning that the total Explained variance value of product quality is able to explain purchasing decisions at the online shop of students of the Management Economics Study Program batch 2020.